Clinical Pathways of Patients Denied Total Knee Arthroplasty Due to an Institutional BMI Cutoff - Wilson, Charlie D.; Lundquist, Kathleen F.; Baruch, Nathan H.; Gaddipati, Ravindra; Hammonds, Kendall A.P.; Allen, Bryce C. (The Journal of Knee Surgery, 2021)
Out of concern for the increased risk of complications with morbid obesity, institutional body mass index (BMI) cutoffs for total knee arthroplasty (TKA) have become commonplace. We sought to answer the questions: what percentage of morbidly obese patients with knee osteoarthritis who present to an arthroplasty clinic will, within 2 years, undergo TKA at (1) a BMI less than 40 kg/m2 or (2) at a BMI greater than 40 kg/m2? Of those who do not undergo surgery, (3) what percentage lose enough weight to become TKA-eligible, and (4) what percentage do not? We performed an observational study of 288 patients, of which 256 had complete follow-up. Institutional electronic medical record review and patient follow-up by telephone were conducted to determine which patients underwent surgery, and at what BMI. For those that did not undergo TKA, BMI was examined to see if the patient ever lost enough weight to become TKA eligible. Twelve of 256 patients (4.7%) underwent TKA at a BMI less than 40 kg/m2, 64 patients (25%) underwent TKA at a BMI greater than 40 kg/m2, and 7 patients (2.7%) underwent surgery at an outside hospital. The average BMI at the time of surgery was 42.3 kg/m2. Thirty-seven of 256 patients (14.4%) lost enough weight to become TKA-eligible within 2 years of the initial visit but did not undergo surgery, while 136 patients (53.1%) neither underwent TKA nor became eligible. Strict enforcement of a BMI cutoff for TKA is variable among surgeons. In the absence of weight loss protocols, 19.1% of morbidly obese patients may be expected to reach the sub-40 kg/m2 BMI milestone.
Keywords: BMI cutoff; obesity; total knee arthroplasty; knee arthroplasty; weight loss